Nursing Students’ Spirituality and Their Perception of Spirituality and Spiritual Care - Putri, Arvianty Shafira; Sunarya, Chiyar Edison; Waluyo, Agung (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
Introduction: The unmet spiritual need in clinical practice is a challenge for nursing education to prepare the spiritual care competence in nursing care. It has been debatable that spiritual nursing competence is derived from the spirituality of nursing students and their perception of spirituality and spiritual care. This study aimed to investigate the relationship between nursing students’ own spirituality and their perception of spirituality and spiritual care.Method: The design of the study was cross-sectional study by involving 286 students from undergraduate and professional program. There were 232 nursing students who participated in this study. The collection data were conducted via online survey using Beliefs and Values Scale (BVS)no and Spiritual Care-Giving Scale (SCGS) tools. The data were analyzed with SPSS. Bivariate analysis with Spearman’s Correlation Coefficient was used to investigate the association between BVS score and SCGS score.Results: The result showed that participants have strong spiritual belief (median: 70) and good perception of spirituality and spiritual care (median: 172). Additionally, a significant relationship of the two variables was found (p-value: 0,000).Conclusions: The spirituality of nursing students should be concerned by nursing education system. This matter seems to be important to prepare nursing students in applying spiritual care in clinical setting.